Synthesis, Characterization, Fluorescence Properties, and DFT Modeling of Difluoroboron Biindolediketonates - Angelo Maspero; Federico Vavassori; Luca Nardo; Guglielmo Vesco; Jenny G. Vitillo; Andrea Penoni (Molecules, 2023)
We report a simple and efficient strategy to enhance the fluorescence of biocompatible biindole diketonates (bdks) in the visible spectrum through difluoroboronation (BF2bdks complexes). Emission spectroscopy testifies an increase in the fluorescence quantum yields from a few percent to as much as >0.7. This massive increment is essentially independent of substitutions at the indole (-H, -Cl, and -OCH3) and corresponds to a significant stabilization of the excited state with respect to non-radiative decay mechanisms: the non-radiative decay rates are reduced by as much as an order of magnitude, from 109 s−1 to 108 s−1, upon difluoroboronation. The stabilization of the excited state is large enough to enable sizeable 1O2 photosensitized production. Different time-dependent (TD) density functional theory (DFT) methods were assessed in their ability to model the electronic properties of the compounds, with TD-B3LYP-D3 providing the most accurate excitation energies. The calculations associate the first active optical transition in both the bdks and BF2bdks electronic spectra to the S0 → S1 transition, corresponding to a shift in the electronic density from the indoles to the oxygens or the O-BF2-O unit, respectively.